Arbitrary-shaped reduced graphene oxide aerogels via an unsaturated water vapor reduction. (30th October 2020) - Shang, Yinxing; Yang, Haoqi; Qin, Zhen; Yin, Shengyan; Yang, Lixue; Xu, Mingwei; Li, Zhiyuan; Jin, Zongqing; Sun, Hang
Abstract: It still remains a challenge to explore facile, economic, and environmental friendly process for the fabrication of graphene aerogels with low density and high purity to meet the various applications. Herein, arbitrary-shaped reduced graphene oxide (rGO) aerogels are prepared by freeze-drying process and followed unsaturated water vapor reduction method staring from GO aqueous suspensions for the first time. Water vapor hydrothermal treatment can decompose all oxygen-containing functional groups in GO and repair GO surface defects effectivly. At higher temperatures (≥175 °C), the carbon in GO may react with water vapor via water-gas shift reaction to form CO, which could also be used as the reductant for the reduction of GO aerogels. The water volume as well as the temperature are key parameters for realizing high reduction degree as well as good shape control of rGO aerogels. Arbitrary shaped rGO aerogels could be prepared by using various molds for freezing GO suspensions. rGO aerogels exhibit a high oil/water separation performance, which could absorb various oils up to 40-55 times of its initial weight with high recyclability. Moreover, the rGO aerogels exhibit typical pressure sensing behavior and excellent energy storage capacitance, which hold great potential applications in flexible pressure sensors and supercapacitors. Graphical abstract: Image 1